PROBABILISTIC ASSESSMENT OF ENVIRONMENTAL POLLUTION BY MODELING OF CHEMICAL ELEMENTS CONTENT’S DISTRIBUTION (ON THE EXAMPLE OF THE POLTAVA REGION’S SURFACE WATERS) - Zhukov, M.; Klypa, A.; Stakhiv, I.; Makarenko, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The comparative assessment of the chemical elements' content distribution in surface waters of the Poltava Region, based on hidrolitochemical surveys of 1985 and 1991–1993, has been conducted. We have found that the most appropriate models of chemical elements' content distribution are a composition lognormal model and lognormal distribution law. It is proved that these models allow to reliably evaluating the areas exceeding critical limits of chemical elements' content. Assessments of these areas for drinking water levels of 10–100 MPC for Ba, Cr etc. have been provided. The size of these areas have increased by 6–60 times during the period mentioned.